Upaya Meningkatkan Berpikir Kritis Siswa Melalui Model Pembelajaran Inkuiri Pada Mata Pelajaran PPKN - Hasrul Muftahid; Deni Andika (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
(Research Action Class In The Class VIII Junior High School Muhammadiyah Labuan) This research aims to improve critical thinking skills of students in the lesson PPKn in students of class VIII JUNIOR HIGH SCHOOL Muhammadiyah Labuan learning model by using Inkuiri. This research is a Research Action Class (PTK). A sampling of research is grade VIII JUNIOR HIGH SCHOOL Muhammadiyah Labuan. Application of the learning model used was Inkuiri by using the techniques in a group discussion. The instruments used are the now the observation sheets, as well as documentation. Data analysis techniques using the percentage of the results the results of the critical thinking of students in the learning process and is supported by the results of the question form given in the end of each meeting of each cycle. This research is carried out in 2 cycle by applying the model Inkuiri. The steps and learning implemented, namely a change in the delivery of the subject matter, students analyze problems, establishment of a discussion group by changing the grouping students based from his achievements, students pair up to discuss, representative groups of students to convey the results of the discussion in front of the class. The results showed that the critical thinking ability of students of class VIII JUNIOR HIGH SCHOOL Muhammadiyah Labuan improved after he used a model of learning inkuiri learning in the PPKn with the subject matter of democracy. This increase is evident in the increased critical thinking ability of students score average of 68.75 in cycles I and rose to 90.18 on cycle II is the result of the sheet now undertaken by students. Students who achieve success criteria have elevated into 39.29% in cycle I and rose to 92.86% in cycle II. Observation results also showed an increase in the student's activities from cycle to cycle I II results from the observation sheet is meeting I of 44.75 meeting to meeting to 57.37 II III and IV the meeting to 67.97 78.35 these results seen from the average score students who obtained, i.e. students increased, among others: students actively in the learning, students are more generous in finding and collecting information is desired, and students also have more opportunity to study with a friend.